Use of conventional DJ stent and single loop stent with string after ureterorenoscopic lithotripsy: Can we use? Can it be effective? - Sharma, Sonu; Sabale, Vilas; Mulay, Abhirudra; Mhaske, Sunil; Satav, Vikram; Nihar, Surya (Urology annals, 2021)
Context: Use of conventional double j stent with string and single loop stent with string after ureterorenoscopy. Aim: The aim of this study was to compare the use of both types of stents using the Ureteral Symptom Score Questionnaire (USSQ) and assess proximal migration. Settings and Design: This was a single institute study. Subjects and Methods: A total of 96 female patients with unilateral ureteric stones were enrolled. Patients underwent ureterorenoscopic lithotripsy, conventional double J (DJ) stent with string and single loop stent with string was placed. Before stent removal at 7-10 days, they were evaluated with X-ray kidney ureter bladder for proximal migration and USSQ for stent-related complaints. Statistical Analysis Used: Data were analyzed using Chi-square and Student's t-test. Results: In our study, Group A (DJ loop with string) had 51 patients and Group B (single J loop with string) had 47 patients. The mean stone size in group A was 10.06 mm and Group B was 9.7 mm. Both groups had one case each of early stent expulsion and none had proximal migration of the stent. Group A had two cases of urinary tract infection and Group B had one case which resolved on antibiotics. Evaluating the USSQ questionnaire in both groups, urinary symptoms such as urgency (P = 0.03), dysuria (P = 0.02), interference with life (P = 0.01), and quality impact overall (P = 0.016) were statistically significant. Evaluating pain, sleep disturbance (P = 0.04), pain at voiding (P = 0.03), and flank pain during voiding (P = 0.018) was statistically significant. In general health, difficulty with heavyweight physical activity (P = 0.02), feeling calm (P = 0.16), social life enjoyment (P = 0.26), and need for extra help (P = 0.008) was significant. In sexual matters, 13 (28%) patients in Group B had no active sex (conscious) and 6 (12%) patients had stopped intercourse due to stent-related symptoms, whereas in Group A, it was 10 (20%) and 2 (4%) patients, respectively. Conclusions: The use of a single J stent with string is an effective method, has lesser complication, and is easier to remove.